Polyurethane material with self-repairing function, and preparation method and application thereof
By introducing aromatic polyaldehyde compounds and hydrazine compounds into polyurethane materials to form a dynamic reversible bond structure, the problem of damage propagation under external force in traditional polyurethane materials is solved, achieving a balance between efficient self-repair and mechanical properties, and is suitable for coatings, seals and elastomer products.
Patent Information
- Application Number
- CN202610742892.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-27
- Publication Date
- 2026-07-10
AI Technical Summary
Traditional polyurethane materials are susceptible to microcracks or structural damage from external impacts, friction, thermal stress, and environmental factors during long-term use, leading to performance degradation. Existing self-healing polyurethane materials have low repair efficiency, demanding conditions, and difficulty in achieving both mechanical and self-healing properties. Furthermore, their repair capabilities after repeated damage and long-term stability are insufficient.
By introducing aromatic polyaldehyde compounds and hydrazine compounds into polyurethane materials to form a dynamic and reversible bond structure, the material can automatically heal after being damaged. A polyurethane material with self-healing function is prepared by mixing polyisocyanates, polyols, chain extenders and aromatic compounds in a specific ratio.
It significantly improves the self-healing ability of polyurethane materials, extends service life, enhances reliability, and combines good mechanical properties and flexibility, making it particularly suitable for coatings, seals, and elastomer products that are subjected to complex stress environments for extended periods.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer materials technology, and in particular to polyurethane materials with self-healing function, their preparation methods and applications. Background Technology
[0002] Polyurethane materials are widely used in coatings, adhesives, sealing materials and elastomers due to their excellent mechanical properties, wear resistance, flexibility and good processing adaptability.
[0003] However, traditional polyurethane materials are susceptible to microcracks or structural damage from external impacts, friction, thermal stress, and environmental factors during long-term use. These damages can gradually expand and lead to a decline in material performance, and in severe cases, even product failure.
[0004] Currently, damage to polyurethane materials is typically addressed through manual repair or complete replacement, which not only incurs high maintenance costs but also affects the continuous performance of equipment or products. With the development of smart and high-durability materials, self-healing polyurethane systems have gradually become a research hotspot. While existing self-healing polyurethane materials can achieve damage repair to some extent, they generally suffer from low repair efficiency, demanding repair conditions, difficulty in balancing mechanical properties and self-healing capabilities, and insufficient dynamic structural stability. Particularly, their repair capabilities after repeated damage and long-term stability remain significantly inadequate. Therefore, there is still a need to develop a novel polyurethane material that combines excellent mechanical properties, stability, and highly efficient self-healing capabilities.
[0005] Therefore, this application is submitted. Summary of the Invention
[0006] To address the aforementioned technical problems, this application provides a self-healing polyurethane material, its preparation method, and its application. This material can self-repair after damage, thereby extending its service life and improving its reliability, while also possessing good mechanical properties, flexibility, and processing adaptability.
[0007] To achieve the objectives of this application, the following technical solution is adopted: This application provides a polyurethane material with self-healing function, characterized in that, by weight parts, it comprises: 20-50 parts of polyisocyanate; 100 parts of polyol; 5-25 parts of aromatic compounds; hydrazine compounds: 3-20 parts; Chain extender: 2-15 parts; The aromatic compound is at least one of terephthalaldehyde, isophthalaldehyde, o-phthalaldehyde, and pyromellitic methyl phthalaldehyde; The hydrazine compound is at least one of carbazide, thiocarbazide, oxaloyl dihydrazine, and malonyl dihydrazine.
[0008] Furthermore, the polyurethane material also includes 1-10 parts of a monoaldehyde compound.
[0009] Furthermore, the monoaldehyde compound is at least one of benzaldehyde, p-methylbenzaldehyde, and salicylaldehyde.
[0010] Furthermore, the polyol is a polyester diol or a polyether diol, and the number average molecular weight of the polyol is 200-2000 g / mol, and the hydroxyl value is 50-600 mg KOH / g.
[0011] Furthermore, the polyisocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate.
[0012] Furthermore, the chain extender is at least one selected from 1,4-butanediol, ethylene glycol, 1,2-propanediol, ethylenediamine, and isophorone diamine.
[0013] This application also provides a method for preparing the polyurethane material as described above, comprising the following steps: Polyols and polyisocyanates are mixed in an inert atmosphere and reacted at 70-90°C for 1-3 hours to obtain isocyanate-terminated prepolymers. A chain extender is added to the prepolymer, and the reaction continues for 0.5-1.5 hours to obtain a polyurethane matrix; The polyurethane matrix is cooled to 60-80°C, and then aromatic compounds and hydrazine compounds are added. The mixture is then melt-blended at a stirring rate of 300-600 rpm for 15-30 minutes to obtain the polyurethane material.
[0014] Furthermore, in the polyurethane matrix, a monoaldehyde compound is first added and mixed for 5-10 minutes, followed by the addition of an aromatic compound and a hydrazine compound.
[0015] Furthermore, after the melt blending is completed, the blend is placed in a mold and hot-pressed at 60-80°C and 10-20MPa pressure for 5-15 minutes, and then naturally cooled to room temperature.
[0016] This application also provides an application of the polyurethane material described above in the preparation of self-healing articles, wherein the self-healing articles are coatings, seals, or elastomers.
[0017] This application has the following technical effects: This application introduces aromatic polyaldehyde compounds and hydrazine compounds into a polyurethane system to form a dynamic and reversible bond structure, enabling the material to automatically heal cracks after being damaged by external forces, thereby significantly improving the self-healing ability of polyurethane materials. Compared to traditional polyurethane materials that can only rely on external repairs, the material of this application can restore its structural integrity through dynamic recombination between molecular chains after damage, effectively reducing the performance degradation caused by microcrack propagation, improving the durability and reusability of the material, and is particularly suitable for coatings, seals, and elastomer products that are subjected to complex stress environments for a long time. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0019] In a first aspect, this application provides a polyurethane material with self-healing function, comprising, by weight parts: 20-50 parts of polyisocyanate; 100 parts of polyol; 5-25 parts of aromatic compounds; hydrazine compounds: 3-20 parts; Chain extender: 2-15 parts; The aromatic compound is at least one of terephthalaldehyde, isophthalaldehyde, o-phthalaldehyde, and pyromellitic methyl phthalaldehyde; The hydrazine compound is at least one of carbazide, thiocarbazide, oxaloyl dihydrazine, and malonyl dihydrazine.
[0020] In some embodiments, the polyurethane material further includes 1-10 parts of a monoaldehyde compound.
[0021] In some embodiments, the monoaldehyde compound is at least one of benzaldehyde, p-methylbenzaldehyde, and salicylaldehyde.
[0022] In some embodiments, the polyol is a polyester diol or a polyether diol, and the number average molecular weight of the polyol is 200-2000 g / mol, and the hydroxyl value is 50-600 mg KOH / g.
[0023] In some embodiments, the polyisocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate.
[0024] In some embodiments, the chain extender is at least one selected from 1,4-butanediol, ethylene glycol, 1,2-propanediol, ethylenediamine, and isophorone diamine.
[0025] Secondly, this application also provides a method for preparing the polyurethane material as described above, comprising the following steps: Polyols and polyisocyanates are mixed in an inert atmosphere and reacted at 70-90°C for 1-3 hours to obtain isocyanate-terminated prepolymers. A chain extender is added to the prepolymer, and the reaction continues for 0.5-1.5 hours to obtain a polyurethane matrix; The polyurethane matrix is cooled to 60-80°C, and then aromatic compounds and hydrazine compounds are added. The mixture is then melt-blended at a stirring rate of 300-600 rpm for 15-30 minutes to obtain the polyurethane material.
[0026] In some embodiments, the polyurethane matrix is first mixed with a monoaldehyde compound for 5-10 minutes, and then an aromatic compound and a hydrazine compound are added.
[0027] In some embodiments, after the melt blending is completed, the blend is placed in a mold and hot-pressed at 60-80°C and 10-20MPa pressure for 5-15 minutes, and then naturally cooled to room temperature.
[0028] Thirdly, this application also provides an application of the above-mentioned polyurethane material in the preparation of self-healing articles, wherein the self-healing articles are coatings, seals or elastomers.
[0029] The following is a detailed explanation using specific embodiments: Example 1 I. Equipment and Pretreatment Reactor: 500mL four-necked flask Stirring: Anchor-type PTFE stirring paddle, 5cm in diameter Heating: Thermostatic oil bath (heat transfer oil is dimethyl silicone oil), temperature control accuracy ±1℃ Vacuum system: Rotary vane vacuum pump, ultimate vacuum ≤0.05mbar, equipped with digital vacuum gauge Atmosphere protection: High-purity nitrogen (purity ≥99.999%), pressure reducing valve outlet pressure 0.1MPa Hot press: Flat plate hot press, temperature control accuracy ±2℃, pressure control accuracy ±0.5MPa Mold: Stainless steel square mold Mold pretreatment: Before use, wipe with acetone and ethanol in sequence, spray with release agent (PTFE dry film lubricant), and dry in an 80℃ oven for 10 minutes.
[0030] II. Detailed Preparation Steps Step 1: Dehydration of polyols Add 100.0g of polytetramethylene ether glycol to a four-necked flask and install a stirrer, thermometer, nitrogen inlet tube, and vacuum port.
[0031] Turn on the mechanical stirrer, set the speed to 150 rpm, start the vacuum pump, and when the vacuum reaches -0.098 MPa, raise the temperature to 110℃.
[0032] Continue dehydration at this temperature and vacuum for 2 hours. Determine the dehydration endpoint by observing that no condensate droplets are produced in the condenser for 10 consecutive minutes and the system stops bubbling. After reaching the endpoint, turn off the vacuum, introduce nitrogen to normal pressure, and lower the oil bath temperature to 70°C.
[0033] Step 2: Prepolymer Synthesis Once the system temperature stabilizes at 70°C, continue purging with nitrogen (flow rate approximately 200 mL / min) and quickly add 35.0 g of isophorone diisocyanate.
[0034] Heat the oil bath to 80°C and the stirring speed to 200 rpm. Start timing the reaction for 2 hours. During the reaction, every 30 minutes, use a glass rod to dip a small amount of the reaction solution into the toluene and observe whether it dissolves quickly.
[0035] Two hours later, a 1.0g sample was taken and the -NCO content was determined by di-n-butylamine titration. The measured value was 5.1%. The obtained product was an isocyanate-terminated prepolymer, which was a colorless, transparent, viscous liquid.
[0036] Step 3: Chain extension reaction Maintain the reaction temperature at 80℃ and the stirring speed at 300 rpm. Add 8.0 g of 1,4-butanediol to a 5 mL glass syringe and use a syringe pump to add it dropwise into the flask at a rate of 0.5 g / min.
[0037] During the dropwise addition, carefully observe the viscosity change of the reaction solution: the viscosity decreases slightly in the initial stage and gradually increases in the later stage. After the dropwise addition is complete, continue the reaction at 80℃ under nitrogen protection for 1 hour. After the reaction is complete, take a small amount of the reactant for Fourier transform infrared spectroscopy: 2270 cm⁻¹ -1 The complete disappearance of the -NCO characteristic absorption peak indicates that the chain extension reaction is complete, yielding a polyurethane matrix, which is a transparent light yellow viscoelastic.
[0038] Step 4: Cool down and add salicylaldehyde Reduce the oil bath temperature to 70°C, add 5.0g of salicylaldehyde, adjust the stirring speed to 400rpm, and mix for 8 minutes.
[0039] Step 5: Add terephthalaldehyde and carbazide Before adding materials, confirm the following: reaction system temperature 70℃, stirring speed 500rpm, and continuous nitrogen protection.
[0040] Feeding sequence and operation: Weigh out 15.0g of terephthalaldehyde powder and add it to the flask in one go within 30 seconds.
[0041] Immediately afterwards, weigh out 10.0g of carbazide powder and slowly sprinkle it into the flask over 30 seconds using a stainless steel spatula.
[0042] Melt blending: After the materials are added, stir at 70°C and 500 rpm for 20 minutes.
[0043] After mixing, turn off the heating and slowly reduce the stirring speed to 100 rpm to remove air bubbles. Turn off the stirring after about 2 minutes.
[0044] Step 6: Hot pressing Mold preparation: Preheat the pre-treated mold to 75°C and place it in the center of the lower platform of the hot press.
[0045] Material transfer: Open the ground glass stopper of the four-necked flask and quickly pour all the molten blend into the mold cavity. Smooth the surface with a stainless steel scraper. The entire process should be completed within 90 seconds to prevent the material from cooling and hardening.
[0046] Hot pressing operation: Close the upper pressure plate of the mold, apply a pre-pressure of 2MPa, and hold for 30 seconds to allow the material to spread evenly.
[0047] Increase the pressure to 15 MPa while observing the small amount of material squeezed out from the mold gap, and maintain hot pressing at 75℃ and 15 MPa for 10 minutes.
[0048] Cooling and demolding: Turn off the heating power of the hot press, maintain a pressure of 15MPa, and allow the mold to cool naturally to room temperature. Record the temperature every 5 minutes during the cooling process. It takes about 30 minutes to drop from 75℃ to 25℃.
[0049] After the mold has completely cooled, release the pressure, open the mold, and gently pry up the polyurethane sheet along the edge with a plastic scraper.
[0050] Experimental Example 1 Experimental samples Experimental group sample: Polyurethane material prepared in Example 1.
[0051] Control group samples: conventional polyurethane materials.
[0052] Both types of samples were pre-prepared as sheets of uniform thickness and cut into standard dumbbell-shaped specimens. Thirty specimens of each type were prepared, of which 10 were used for original mechanical property testing, 10 for self-healing performance testing, 5 for microstructure observation, and 5 were kept as spares.
[0053] All samples were conditioned for 24 hours in a constant temperature and humidity environment of 23±2℃ and 50±5% before testing to eliminate the influence of internal stress and environmental differences on the test results.
[0054] II. Original Mechanical Property Testing (Undamaged State) 2.1 Test Parameter Settings Turn on the universal testing machine and preheat for 30 minutes to ensure system stability: Tension rate: 50 mm / min Initial fixture spacing: 40mm Load sensor: 5kN range Data acquisition frequency: 10Hz Test mode: Single stretch to fracture 2.2 Test Operation Steps Five specimens (EX1-T-01 to EX1-T-05) from the original tensile test group were taken and tested sequentially: Clamp the two ends of the specimen smoothly into the upper and lower clamps of the universal testing machine, ensuring that the specimen is vertically aligned and not tilted. Set the clamping force to 0.3 MPa to avoid slipping or damaging the specimen.
[0055] Adjust the position of the upper clamp so that the sample is in a naturally straight state but not under tension, at which point the force value is zero.
[0056] Confirm that the initial distance between the two baselines is 25mm. If the deviation exceeds 1mm, reinstall.
[0057] The tensile program is started, and the specimen is stretched at a speed of 50 mm / min. The computer records the tensile force and displacement data simultaneously.
[0058] Observe the deformation behavior of the specimen during the tensile process, including necking, the appearance and expansion of the stress whitening area, and the final fracture location.
[0059] At the moment the specimen breaks, the system automatically records the maximum tensile load and the displacement at the moment of fracture.
[0060] Remove the fractured sample, observe the fracture morphology, and take photos for recording.
[0061] Clean the fixture and proceed with the testing of the next sample.
[0062] The original tensile test group of the control group consisted of 5 specimens (CP1-T-01 to CP1-T-05) that were tested using the same method.
[0063] The original tensile strength and elongation at break were calculated separately for each specimen. The average value and standard deviation of the five specimens in each group were then taken.
[0064] The final test results are shown in Tables 1 and 2 below.
[0065] Table 1 Original tensile test results of the implementation group Table 2 Original tensile test data for the comparison group III. Procedures to Introduce Scratch Damage 3.1 Marking the location of scratches Five samples (EX1-H-01 to EX1-H-05) from the new Example 1 self-healing test group and five samples (CP1-H-01 to CP1-H-05) from the Comparative Example 1 self-healing test group were taken.
[0066] At the very center of the test area of each specimen, use a fine marker to draw a line perpendicular to the length of the specimen as the starting point for the scratch.
[0067] Operating steps: Place the sample into the positioning groove of the base with the test surface facing up, and align the scratch mark line with the center scale line of the guide block.
[0068] Mount the scalpel blade onto the holder with the tip pointing downwards. Rotate the micrometer adjustment mechanism until the tip just touches the sample surface (the depth reading is 0 at this point). Record the micrometer reading at this moment as the zero point.
[0069] Continue rotating the micrometer until the blade extends downwards by 1.00 mm (corresponding to 50% of the 2 mm sample thickness).
[0070] Tighten the blade holder and push the guide block to slide across the sample surface at a constant speed along the guide groove. The blade cuts a scratch on the sample perpendicular to the length direction.
[0071] After the cutting is completed, raise the blade and remove the sample.
[0072] 3.3 Scratch Quality Inspection The scratch depth of each specimen was measured at multiple points using a depth gauge: Take three points on the left, middle, and right along the length of the scratch; Measure three times at each location and take the average value; The required scratch depth is 1.00±0.05mm, and the scratch width is approximately 0.2-0.3mm. If the scratch depth of a sample exceeds the range, the sample shall be rejected, and the scratching operation shall be repeated with a spare sample.
[0073] Use an optical microscope (100x magnification) to observe the morphology of the scratched area and take photos to record the geometric characteristics of the scratch, including: the continuity of the scratch, the neatness of the edges, and whether there are defects such as burrs or tears. A qualified scratch should present a continuous and neat V-shaped or U-shaped groove with no obvious damage to the edges.
[0074] After the scratch introduction and quality inspection are completed, all scratched samples are put back into the constant temperature and humidity chamber and left to stand for 1 hour at 23±2℃ to eliminate local stress and heat that may be generated during the scratching process.
[0075] IV. Healing Process 4.1 Preparation of the healing environment Set the temperature of the forced-air drying oven to 80℃ and start preheating. Place a flat, high-temperature resistant glass plate (200×200×5mm) inside the drying oven. The surface of the glass plate should be wiped clean with anhydrous ethanol and dried beforehand to ensure it is free of dust and oil contamination.
[0076] A thermocouple temperature probe is placed inside the drying oven near the glass plate and connected to an external temperature recorder to monitor the actual temperature near the sample in real time. Simultaneously, an infrared thermal imager is set up with its lens aimed at the center of the glass plate to record the temperature distribution changes on the sample surface during the healing process.
[0077] Healing treatment can only be carried out after the temperature of the drying oven has stabilized at 80±1℃ and has been maintained for at least 30 minutes.
[0078] 4.2 Sample Placement Place the scratched sample on a glass plate according to the following requirements: All samples were placed with the test surface facing upwards. Maintain a distance of at least 20 mm between samples to avoid contact with each other. Samples must not be stacked. The total number of samples on the glass plate should not exceed 10 to ensure smooth hot air circulation. The experimental and control group samples were placed on glass plates in different areas, but were treated with the same drying oven and temperature conditions to ensure consistency of treatment conditions.
[0079] 4.3 Monitoring of the healing process Close the drying oven door and start timing the healing process, setting it to 24 hours.
[0080] During the healing process, temperature data and observations were recorded at the following time points: 0, 0.5, 1, 2, 4, 6, 8, 12, 16, 20, 24 hours At each recording point, check the sample condition through the observation window of the drying oven, and simultaneously record the thermocouple temperature and the temperature distribution displayed by the infrared thermal imager. Carefully observe the scratched area for any significant changes, such as a reduction in scratch width or a color change, but do not open the door to disturb the sample.
[0081] The data recorded by the infrared thermal imager includes the highest, lowest, and average temperatures of the test area. All samples must maintain a surface temperature between 78-82°C during the healing process. If the temperature in any area deviates from this range, the airflow distribution inside the drying oven must be adjusted or the sample positions rearranged.
[0082] After 24 hours of healing treatment, turn off the power to the drying oven, but do not open the oven door, allowing the sample to cool naturally with the oven. Once the temperature inside the oven has dropped below 40°C (approximately 1.5 hours), open the door and remove the sample.
[0083] The removed sample was placed in a constant temperature and humidity chamber and conditioned for 2 hours at 23±2℃ and 50±5% relative humidity to allow the sample to fully recover to room temperature and stabilize.
[0084] V. Tensile strength test after healing 5.1 Pre-test checks Before the tensile test begins, the following checks are performed on each healed specimen: Visually inspect the sample to check for overall integrity, and for any unexpected breaks or obvious defects.
[0085] The morphology of the scratch-healed area was observed using an optical microscope (100x magnification), and photomicrographs were taken to record the degree of scratch healing (such as whether the groove was filled or whether the interface disappeared).
[0086] Use a thickness gauge to measure the thickness of the healed area of the scratch and compare it with the original thickness to determine whether there is material loss or expansion.
[0087] 5.2 Tensile Test The instruments, parameters, and operating procedures for the post-healing tensile strength test are exactly the same as those for the original mechanical property test (Part 5), as follows: Preheat the universal testing machine for 30 minutes, set the tensile rate to 50 mm / min, and the initial clamping distance to 40 mm.
[0088] Install the healed specimens (EX1-H-01 to EX1-H-05, CP1-H-01 to CP1-H-05) sequentially into the fixture, ensuring alignment.
[0089] Adjust the upper clamp to allow the sample to straighten naturally and the force value to return to zero.
[0090] Confirm that the initial distance between the two baselines is 25mm.
[0091] Start the tensile test until the specimen breaks.
[0092] Record the maximum tensile load and fracture displacement.
[0093] Calculate the tensile strength and repair efficiency after healing.
[0094] The final experimental results are shown in Tables 3 and 4 below.
[0095] Table 3. Tensile test data of the experimental group after healing. Table 4. Tensile test data of the comparison group after healing. Based on the experimental results given above, in terms of the original mechanical properties, the original tensile strength of the experimental group was 26.8 MPa, slightly lower than that of the control group (28.4 MPa). Although this difference exists, it is not significant. The strength of the experimental group maintained about 94% of that of conventional polyurethane, indicating that the dynamic acylhydrazone network formed by the introduction of terephthalaldehyde and carbamate did not cause significant damage to the skeletal structure of polyurethane, and the material still has good load-bearing capacity.
[0096] More notably, the experimental group achieved an elongation at break of 507.6%, while the control group only reached 419.4%, with the former being approximately 21% higher. This indicates that the introduction of dynamic bonds did not make the material brittle; on the contrary, it enhanced the mobility and flexibility of the molecular chain segments to some extent. This phenomenon can be explained from a structural perspective: in the polyurethane matrix, the acylhydrazone bonds formed by the reaction of aromatic compounds and hydrazine compounds are reversible dynamic covalent bonds. They remain stable at room temperature, but when the molecular chains are subjected to tensile stress, these dynamic bonds can dissipate energy through reversible breakage and recombination, delaying chain segment breakage caused by stress concentration, thus enabling the material to withstand greater deformation without failure. In contrast, the control group only has traditional urethane bonds and physical cross-linking points, lacking this energy dissipation mechanism, hence its relatively lower elongation at break. In this sense, the experimental group achieved better toughness while maintaining higher tensile strength, demonstrating the unique regulatory role of dynamic covalent bonds in the mechanical properties of polyurethane.
[0097] In terms of self-healing performance, after experiencing scratches 50% of the thickness in depth and undergoing 24 hours of healing treatment at 80℃, the experimental group achieved a tensile strength of 23.5 MPa after healing, with a repair efficiency as high as 87.6%. This means that the material almost recovered 90% of its original strength, and the structural integrity and mechanical load-bearing capacity of the scratched area were effectively reconstructed. In contrast, under the same damage and healing conditions, the control group only achieved a tensile strength of 3.18 MPa after healing, with a repair efficiency of only 11.2%. This indicates that almost no substantial healing occurred at the scratch site, and the material's mechanical properties were severely degraded to the point where it could hardly withstand normal tensile loads. The reason for this stark difference lies in the fundamental difference in the chemical structure design of the two materials. The control group is a conventional thermosetting or linear polyurethane, whose molecular chains are irreversibly cross-linked by covalent bonds or physically entangled. Once a scratch breaks the molecular chain, the broken chain ends cannot automatically reconnect. Even under high-temperature conditions, only weak intermolecular forces or random contact of chain segments can produce extremely limited surface bonding, resulting in extremely low repair efficiency. In the experimental group, terephthalaldehyde and carbazone formed a dynamic acylhydrazone network in the polyurethane matrix. These bonds can undergo reversible breaking and exchange reactions when stimulated by external factors (such as heating). The unreacted aldehyde and hydrazine groups exposed at the scratched surface, as well as the broken acylhydrazone bonds, can undergo a condensation reaction, thus reconnecting the two previously separated surfaces into a complete network structure. The healing temperature of 80℃ provides sufficient activation energy for this dynamic exchange, enabling the molecular chains to acquire the necessary mobility, accelerating the collision and reaction of functional groups at the interface, and ultimately achieving efficient interfacial fusion and restoration of mechanical properties.
[0098] In summary, whether considering macroscopic mechanical property data or repair efficiency calculations, the experimental group demonstrated a self-healing ability far exceeding that of the control group. This fully proves that the scheme proposed in this application, which involves simultaneously introducing aromatic polyaldehyde compounds and hydrazine compounds into the polyurethane system to construct a dynamic acylhydrazone bond network, indeed endows traditional polyurethane materials with highly efficient self-healing capabilities that were not originally present, while also maintaining good mechanical properties. Compared with existing conventional polyurethane materials, it exhibits outstanding substantial characteristics and significant progress, fully meeting the requirements for inventive step evaluation.
[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the technical solutions of the embodiments of this application.
Claims
1. A polyurethane material with self-healing function, characterized in that, By weight, it includes: 20-50 parts of polyisocyanate; 100 parts of polyol; 5-25 parts of aromatic compounds; hydrazine compounds: 3-20 parts; Chain extender: 2-15 parts; The aromatic compound is at least one of terephthalaldehyde, isophthalaldehyde, o-phthalaldehyde, and pyromellitic methyl phthalaldehyde; The hydrazine compound is at least one of carbazide, thiocarbazide, oxaloyl dihydrazine, and malonyl dihydrazine.
2. The polyurethane material with self-healing function according to claim 1, characterized in that, The polyurethane material also includes 1-10 parts of a monoaldehyde compound.
3. The polyurethane material with self-healing function according to claim 2, characterized in that, The monoaldehyde compound is at least one of benzaldehyde, p-methylbenzaldehyde, and salicylaldehyde.
4. The polyurethane material with self-healing function according to claim 1, characterized in that, The polyol is a polyester diol or a polyether diol, and the number average molecular weight of the polyol is 200-2000 g / mol, and the hydroxyl value is 50-600 mg KOH / g.
5. The polyurethane material with self-healing function according to claim 1, characterized in that, The polyisocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, and hexamethylene diisocyanate.
6. The polyurethane material with self-healing function according to claim 1, characterized in that, The chain extender is at least one selected from 1,4-butanediol, ethylene glycol, 1,2-propanediol, ethylenediamine, and isophorone diamine.
7. A method for preparing the polyurethane material according to any one of claims 1-6, characterized in that, Includes the following steps: Polyols and polyisocyanates are mixed in an inert atmosphere and reacted at 70-90°C for 1-3 hours to obtain isocyanate-terminated prepolymers. A chain extender is added to the prepolymer, and the reaction continues for 0.5-1.5 hours to obtain a polyurethane matrix; The polyurethane matrix is cooled to 60-80°C, and then aromatic compounds and hydrazine compounds are added. The mixture is then melt-blended at a stirring rate of 300-600 rpm for 15-30 minutes to obtain the polyurethane material.
8. The preparation method according to claim 7, characterized in that, In the polyurethane matrix, a monoaldehyde compound is first added and mixed for 5-10 minutes, followed by the addition of an aromatic compound and a hydrazine compound.
9. The preparation method according to claim 7, characterized in that, After the melt blending is completed, the blend is placed in a mold and hot-pressed at 60-80℃ and 10-20MPa pressure for 5-15 minutes, and then naturally cooled to room temperature.
10. The use of the polyurethane material as described in any one of claims 1-6 in the preparation of a self-healing article, wherein the self-healing article is a coating, a sealant, or an elastomer.